2015
DOI: 10.18632/oncotarget.6729
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic cell death caused by follistatin-like 1 inhibition is associated with up-regulated Bim by inactivated Erk1/2 in human lung cancer cells

Abstract: Follistatin-like 1 (FSTL1) was identified as a novel pro-inflammatory protein showing high-level expression in rheumatoid arthritis. The protective effect of FSTL1 via the inhibition of apoptosis was reported in myocardial injury. However, the functional mechanism of FSTL1 in cancer is poorly characterized, and its proliferative effects are ambiguous. Here, we examined the effects of FSTL1 on cellular proliferation and cell cycle checkpoints in lung cancer cells. FSTL1 inhibition induced the cellular portion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…FSTL1 has previously been reported to play both oncogenic and tumor-suppressive roles in various cancer types (23)(24)(25)(26)(27)(28)(29)(30). Yet, to the best of our knowledge, this is the first study to report its significance in ESCC.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…FSTL1 has previously been reported to play both oncogenic and tumor-suppressive roles in various cancer types (23)(24)(25)(26)(27)(28)(29)(30). Yet, to the best of our knowledge, this is the first study to report its significance in ESCC.…”
Section: Discussionmentioning
confidence: 78%
“…However, FSTL1 was found to be overexpressed in astrocytic brain tumors (27) and also to enhance the metastasis of cancer cells in breast, prostate, skin, and pancreatic cancers (28)(29). A recent study have also found knockdown of FSTL1 to induce mitotic cell death and BIM upregulation in nonsmall cell lung carcinoma cells (30). However, to date, the clinical significance and functional role of endogenous and secretory FSTL1 and the molecular mechanism by which it drives ESCC pathogenesis has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…3) FSTL1 (follistatin-like 1) is a putative activin-binding protein. Knockdown of FSTL1 in lung cancer cells resulted in mitotic arrest followed by apoptosis promoted by the activation of caspase-3 and -9 (Bae et al, 2016). FSTL1 is downregulated during cellular senescence of human mesenchymal stem cells (Yoo, Choi, & Kim, 2013).…”
Section: '-A C C a A A U G U A C A A C A A A C U -5'mentioning
confidence: 99%
“…An increasing number of studies have indicated that the secreted protein FSTL1 plays key roles in cardiovascular diseases and might be involved in the pathogenesis of cancer . However, it is not clear whether FSTL1 is involved in breast cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have indicated that the secreted protein FSTL1 plays key roles in cardiovascular diseases and might be involved in the pathogenesis of cancer. [22][23][24][25] However, it is not clear whether FSTL1 is involved in breast cancer development and progression. Excessive proliferation plays a critical role in tumor growth; therefore, in this study we tested the effects of FSTL1 on proliferation of BT-549 breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%